2015
DOI: 10.1130/g36262.1
|View full text |Cite
|
Sign up to set email alerts
|

Sticky stuff: Redefining bedform prediction in modern and ancient environments

Abstract: The dimensions and dynamics of subaqueous bedforms are well known for cohesionless sediments. However, the effect of physical cohesion imparted by cohesive clay within mixed sand-mud substrates has not been examined, despite its recognized influence on sediment stability. Here we present a series of controlled laboratory experiments to establish the influence of substrate clay content on subaqueous bedform dynamics within mixtures of sand and clay exposed to unidirectional flow. The results show that bedform d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 20 publications
1
83
0
1
Order By: Relevance
“…Although a simple relationship between suspended clay concentration in flows and the percentage mud matrix in the resultant deposits does not exist, and bed clay fractions are not available for the present experiments, it is likely that bedforms are modified at a concentration appreciably lower than 15% mud in the matrix. This was confirmed by Baas et al (2013), who showed that current ripples are almost fully suppressed at a depth-averaged flow velocity of c. 0.4 m s −1 and bed clay fractions above 13%, by Schindler et al (2015) for dunes, where even small amounts of clay in the bed showed dramatic effects on bedform size, and by Whitehouse et al (2000), whose data compilation shows that 5-15% clay is sufficient to change from bed-flow interaction dominated by non-cohesive processes to bed-flow interaction dominated by cohesive processes. It is therefore evident that in future research, even the smallest primary mud fractions in sandstones that possess primary current stratification should be considered in the reconstruction of flow dynamics and depositional processes.…”
Section: Main Applicationsmentioning
confidence: 59%
See 3 more Smart Citations
“…Although a simple relationship between suspended clay concentration in flows and the percentage mud matrix in the resultant deposits does not exist, and bed clay fractions are not available for the present experiments, it is likely that bedforms are modified at a concentration appreciably lower than 15% mud in the matrix. This was confirmed by Baas et al (2013), who showed that current ripples are almost fully suppressed at a depth-averaged flow velocity of c. 0.4 m s −1 and bed clay fractions above 13%, by Schindler et al (2015) for dunes, where even small amounts of clay in the bed showed dramatic effects on bedform size, and by Whitehouse et al (2000), whose data compilation shows that 5-15% clay is sufficient to change from bed-flow interaction dominated by non-cohesive processes to bed-flow interaction dominated by cohesive processes. It is therefore evident that in future research, even the smallest primary mud fractions in sandstones that possess primary current stratification should be considered in the reconstruction of flow dynamics and depositional processes.…”
Section: Main Applicationsmentioning
confidence: 59%
“…Wang et al 1988;Liang et al 2007). The available data suggest that these mixedsediment bedforms are smaller than in pure sand, even at clay bed fractions below 3% (Basaniak & Verhoeven 2008;Baas et al 2013;Schindler et al 2015;Fig. 8).…”
Section: Bedforms and Primary Current Stratification In Cohesive Sedimentioning
confidence: 97%
See 2 more Smart Citations
“…Biofilms have been shown to play a fundamental role in sediment dynamics and the subsequent diagenesis of marginal marine sedimentary systems (Stal, 2003), affecting grain-size heterogeneity (Garwood et al, 2015), sediment stability (Vignaga et al, 2013), sediment transport, and bedform stability Schindler et al, 2015). Intertidal biofilms typically result from the secretion of extracellular polymeric substances (EPSs) (adhesive mucilage) by microphytobenthic (MPB) communities that are composed of algae (diatoms, euglenids, crysophyceans, dinoflagellates), cyanobacteria, and other photosynthetic bacteria (Jesus et al, 2009).…”
Section: Introductionmentioning
confidence: 99%